2012
DOI: 10.1172/jci46215
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockade attenuates cigarette smoke–induced lung injury and rescues lung architecture in mice

Abstract: Chronic obstructive pulmonary disease (COPD) is a prevalent smoking-related disease for which no diseasealtering therapies currently exist. As dysregulated TGF-β signaling associates with lung pathology in patients with COPD and in animal models of lung injury induced by chronic exposure to cigarette smoke (CS), we postulated that inhibiting TGF-β signaling would protect against CS-induced lung injury. We first confirmed that TGF-β signaling was induced in the lungs of mice chronically exposed to CS as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 73 publications
(74 reference statements)
6
96
1
4
Order By: Relevance
“…retinoic acid), while initially required to promote re-differentiation and related reactivation of abnormal features, finally reverses the epithelial phenotype by affecting epigenetic modifications [41]. Finally, targeting TGF-β1 was able to decrease mesenchymal features in vitro, in line with previous studies where anti-TGF-β treatment was able to improve both airway pathology and emphysema [42].…”
Section: Discussionsupporting
confidence: 82%
“…retinoic acid), while initially required to promote re-differentiation and related reactivation of abnormal features, finally reverses the epithelial phenotype by affecting epigenetic modifications [41]. Finally, targeting TGF-β1 was able to decrease mesenchymal features in vitro, in line with previous studies where anti-TGF-β treatment was able to improve both airway pathology and emphysema [42].…”
Section: Discussionsupporting
confidence: 82%
“…Although several studies have shown that antagonism of angiotensin II signaling results in decreased TGF-b signaling in a variety of tissues, including kidney, lung, skeletal muscle, heart, and aorta (Shihab et al 1997;Sun et al 1998;Lavoie et al 2005;Habashi et al 2006;Yao et al 2006;Cohn et al 2007;Podowski et al 2012), the exact mechanism by which this occurs is not fully understood (Gibbons et al 1992;Stouffer and Owens 1992;Wolf et al 1993Wolf et al , 1999Kagami et al 1994;Lee et al 1995;Campbell and Katwa 1997;Fukuda et al 2000;Boffa et al 2003;Naito et al 2004;RodriguezVita et al 2005;Zhou et al 2006;Chen et al 2013). Suppression of excessive Erk1 and Erk2 MAPK activation with losartan or an inhibitor of MAPK kinase (MAPKK, also known as MEK) has been shown to normalize aortic architecture and aneurysm pathology in MFS mouse models (Habashi et al 2011), indicating that Erk MAPK activation is critical to aneurysm progression.…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 99%
“…Morphometric studies were performed as previously described (19,20) on mice exposed to O2 for 4 days. Further details are provided in the online supplement Immunohistochemistry Immunohistochemistry (IHC) was performed as previously described (20).…”
Section: Morphometrymentioning
confidence: 99%